Saturday

March 28, 2015

March 28, 2015

Posted by **Breanna** on Wednesday, November 28, 2012 at 10:33am.

2) which expression is equivalent to (sin x+1) (sin x -1)?

A. Cos^2x

B. -cos^2x

C. Cos^2x+1

D. Cos^2x-1

E. -cos^2x-1

- Calculus (help Steve plz) -
**Steve**, Wednesday, November 28, 2012 at 10:44am1. whassup? just a simple vector

|w| = √(8^2+15^2) = 17

since (sin+1)(sin-1) = sin^2 - 1

and cos^2 = 1-sin^2,

you have -cos^2 x

**Answer this Question**

**Related Questions**

TRIG! - Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6...

algebra - Can someone please help me do this problem? That would be great! ...

Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...

tigonometry - expres the following as sums and differences of sines or cosines ...

Math - Calculus - The identity below is significant because it relates 3 ...

pre-cal - Simplify the given expression........? (2sin2x)(cos6x) sin 2x and cos ...

calculus - Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x...

trig - Reduce the following to the sine or cosine of one angle: (i) sin145*cos75...

Calc. - Differentiate. y= (cos x)^x u= cos x du= -sin x dx ln y = ln(cos x)^x ln...

trig - The expression 4 sin x cos x is equivalent to which of the following? (...